Success with Your Early Years Research Project - Solvason Carla; Walker Rosie (Sage, 2014)
This book is a practice for creative thinking for new tomorrows; the book shows us how to do this, and is to be commended for anyone who wishes to find innovative ways to thing and act for all new beginnings. List of Figures and Tables, Acknowledgements, Foreword, Introduction, Considering Your Research Question, Theoretical Framework, Taking an Ethical Stance, Literature Review, Methodology: Choosing Your Research Approach, Gathering Data, Data Analysis, Reaching Conclusions and Reflecting, Disseminating Findings, Final Reflection on the Qualities of a Practitioner Researcher, References, Index.